PARTISIPASI MASYARAKAT DAN MODAL SOSIAL DALAM PEMBANGUNAN - Hari Harjanto Setiawan (Politeknik Kesejahteraan Sosial, 2009)
Social participation of community in social welfare services is one of interested to social problem in social environment. Social participation is bottom up from planing, action, budgeting to evaluation. social capital is a set of informal values or norms shared among members of a group that permits cooperation among them. Social capital is generally referred to as the set of trust, institutions, social norms, social networks, and organizations that shape the interactions of actors within a society and are an asset for the individual and collective production of well-being. At the macro level, social capital can affect the economic performance and the processes of eco- nomic growth and development. This papper to dercribe about social participation in the community.Keywords : Participation, SocialCapital, Development